1969
DOI: 10.1128/aem.18.3.355-359.1969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Media for Differentiating Nonfermenting Gram-negative Bacteria of Medical Significance

Abstract: An evaluation was made of media and tests used for differentiating nonfermenting gram-negative bacteria encountered in medical bacteriology in order to determine those diagnostic procedures most useful in identifying these bacteria. The organisms examined included Alcaligenes faecalis, A. odorans var. viridans, Moraxella duplex (Mima polymorpha var. oxidans), Acinetobacter anitratum (Herellea vaginicola), A. Iwoffi (Mima polymorpha), Pseudomonas fluorescens, P. putida, P. maltophilia, P. pseudomallei, P. stutz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This was expected because bacterial species respond differently to environmental stresses. It was reported that P. aeruginosa does not tolerate 6.5% NaCl (Gilardi 1969) whilst E. faecalis was reported to be more resistant to NaCl (Lee 1972, Faklam 1973).…”
Section: Discussionmentioning
confidence: 99%
“…This was expected because bacterial species respond differently to environmental stresses. It was reported that P. aeruginosa does not tolerate 6.5% NaCl (Gilardi 1969) whilst E. faecalis was reported to be more resistant to NaCl (Lee 1972, Faklam 1973).…”
Section: Discussionmentioning
confidence: 99%